Electromagnetic induction and surface impedance in a half-space from an overhead moving current system. - Hsueh-Yuan Pao (IEEE Transactions on antennas and propagation)
How does an overhead current system having a velocity v influence the electromagnetic (EM) fields and the surface impedance as measured on the ground? We attempt to answer this question in this paper. A formulation is given for the fields produced by a current system having a uniform translational velocity. The numerical results that reflect the influence of velocity on the surface impedance at the air/earth boundary are presented. The relativity effect is not considered